2019
DOI: 10.1681/asn.2019050502
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function Decline among Black Patients with Sickle Cell Trait and Sickle Cell Disease: An Observational Cohort Study

Abstract: BackgroundSickle cell trait and sickle cell disease are thought to be independent risk factors for CKD, but the trajectory and predictors of kidney function decline in patients with these phenotypes are not well understood.MethodsOur multicenter, observational study used registry data (collected January 2005 through June 2018) and included adult black patients with sickle cell trait or disease (exposures) or normal hemoglobin phenotype (reference) status (ascertained by electrophoresis) and at least 1 year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 66 publications
2
31
1
Order By: Relevance
“…Another recent observational study included 1251 black adult patients with sickle cell trait, 230 with sickle cell disease, and 8729 reference patients, with a median follow-up of 8 years. 5 Sickle cell trait and disease are associated with faster eGFR decline in black patients, with faster decline in sickle cell disease. 5 African American donor ethnicity is one of 10 risk factors in calculating the kidney donor profile index used in assessing organ quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another recent observational study included 1251 black adult patients with sickle cell trait, 230 with sickle cell disease, and 8729 reference patients, with a median follow-up of 8 years. 5 Sickle cell trait and disease are associated with faster eGFR decline in black patients, with faster decline in sickle cell disease. 5 African American donor ethnicity is one of 10 risk factors in calculating the kidney donor profile index used in assessing organ quality.…”
Section: Discussionmentioning
confidence: 99%
“…5 Sickle cell trait and disease are associated with faster eGFR decline in black patients, with faster decline in sickle cell disease. 5 African American donor ethnicity is one of 10 risk factors in calculating the kidney donor profile index used in assessing organ quality. A recent study evaluated outcomes of deceased-donor kidney transplants from African American donors stratified by kidney donor profile index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local hypoxia in a restricted area, for example, during a vaso-occlusive crisis, increases their polymerization capacity and instability and induces massive, intravascular hemolysis which can alter renal structure and function [ 121 , 122 ]. Both SCA and its heterozygous state (sickle cell trait, with an attenuated phenotype), are associated with an increased risk of CKD [ 123 ]. In addition to sickle cell susceptibility to hemolysis, HbS is unstable and prone to auto-oxidation and release of its cofactor heme.…”
Section: Ho-1 In Kidney Diseasesmentioning
confidence: 99%
“…Furthermore, prior studies have only examined patients in whom ESKD was caused by SCD (SCD-ESKD) [6, 8] instead of ESKD patients with concurrent SCD (SCD with ESKD). This is important because recent studies have shown that severe phenotypes of SCD and SCD patients with more frequent hospitalizations for pain episodes tend to have a faster decline in GFR [17, 18]. This implies that prior studies which examined outcomes in ESKD caused by SCD may have been biased by the most severe SCD phenotypes.…”
Section: Introductionmentioning
confidence: 99%